Специфіка жанрового і стильового аналізу літературного твору з міфологічними структурами у школі - Сидоренко, Юлія Олександрівна (My University, 2019)
У статті актуалізується потреба адаптації жанрового і стильового аналізу до роботи з творами міфологічного змісту на уроках української літератури. Розроблено методичну модель вивчення у 9-11 класах творів з міфологічними структурами на основі їх жанрової та стильової природи. Метою такої діяльності стає навчити учнів досліджувати художню версію в межах обраного автором жанру і стилю та сформувати у старшокласників ряд спеціальних умінь та навичок роботи з літературним матеріалом. Автор акцентує увагу на ролі міфологізму в утворенні різних жанрів та осмисленні концепції різних літературних напрямків. Навчальна діяльність включає в себе три основні етапи. Кожен етап характеризується специфічним використанням методів і видів робіт. Подаються зразки завдань, які вчителі-словесники можуть використовувати у своїй практиці.
THE SPECIFICITY OF GENRE AND STYLE ANALYSIS OF LITERARY WORKS WITH MYTHOLOGICAL STRUCTURES IN SCHOOL
The author focuses on the role of mythologism in the formation of different genres and understanding the concept of different literary trends. The literary base for construction the educational process of studying a certain group of works is theoretically substantiated and points to previous achievements of methodologists. Educational activity includes three main stages: formation of new knowledge, skills, their application and generalization and systematization of acquired knowledge and skills. Each stage is characterized by the specific usage of general didactic metholodical-literary methods and types of works that are cognitive and developing. The particular attention is paid to the work of students with literary and critical materials, the argumentation of judgments of scientists. The author of the article notes that the effectiveness of the educational process in the sense and literary direction. The article actualizes the need of adaptation of genre and style analysis to work with texts that contain the mythological content on the literature lessons. The methodical model of study in 9-11 form of the texts with mythological structures based on their genre and style nature is made. In the article we consider the following works of the school program: ballads “Prychynna”, “Topolia”, by T. Shevchenko, feerie “Lisova Pisnia” by Lesia Ukrainka, dramatic scetch “Po dorozi v kazku” by O. Oles, novel-ballad “Dim na hori” by Val. Shevchuk. The purpose of the lesson is to teach students to explore the artistic version within the genre and style chosen by the author and develop a member of special literary skills of senior pupils. The article provides examples of tasks that vocabulary teachers can use in their practice. The proposed approach extends the methodology of style and genre research of works of Ukrainian literature trough in-depth analysis of mythodological structures. Publication materials can be used by teachers while Ukrainian literature lessons in 9-11 grades.
Keywords: жанровий аналіз, стильовий аналіз, міфологічні структури, міфопоетика, літературний стиль